Hubungan Antara Konsumsi Rutin Daun Kelor Rebus dan Pengendalian Gula Darah pada Pasien Diabetes Melitus Tipe 2 - Marwida Ida; Suparta Mahmuddin; Ismail Ismail (Celebes Health Journal, 2026)
Background: Diabetes mellitus is a global health problem characterized by elevated blood glucose levels and associated with serious complications. Achieving optimal glycemic control remains challenging, highlighting the need for accessible non-pharmacological interventions such as herbal remedies. Objective: This study aimed to analyze the relationship between the consumption of moringa leaf decoction and blood glucose control among patients with diabetes mellitus. Methods: A quantitative study with a cross-sectional design was conducted in Pakeng Village, Lembang District, Pinrang Regency, from March to April 2026. A total of 50 respondents were selected using purposive sampling. Data were collected through structured interviews and blood glucose measurements using a digital glucometer. Statistical analysis included descriptive statistics, chisquare test, and logistic regression with a significance level of p<0.05. Results: The findings showed that respondents who routinely consumed moringa leaf decoction had a higher proportion of controlled blood glucose levels compared to those who did not. Logistic regression analysis indicated that moringa consumption was a significant factor (p=0.012; OR=4.26) in improving glycemic control. Conclusions: Routine consumption of moringa leaf decoction is significantly associated with improved blood glucose control, suggesting its potential as an effective non-pharmacological intervention in diabetes management.